Cancer and sexual health - Mulhall, John P.; Incrocci, Luca 1962-.; Goldstein, Irwin; Rosen, Ray 1946-.; SpringerLink (Online service). (New York Humana Press, 2011)
The average physician and even cancer care-givers are not knowledgeable about the effects of cancer treatment on sex and reproductive life. They are even less aware of the options available for treatment of such patients. Cancer and Sexual Health fills a great need for a reference work devoted to the link between cancer and human sexuality. The volume is designed to give a comprehensive and state-of-the-art review of the sexual and reproductive consequences of cancer diagnosis and treatment. It will prove an invaluable resource for those clinicians caring for cancer patients as well as acting as a reference text for the sexual medicine clinician who may not see a large number of cancer patients.
Functional Anatomy of the Male Sex Organs -- Functional Anatomy of the Female Sex Organs -- Physiology of Libido -- Physiology of Orgasm -- Physiology of Female Genital Sexual Arousal -- Physiology of Erection -- Physiology of Ejaculation -- Classifying Female Sexual Dysfunction -- Hypoactive Sexual Desire Disorder -- Disorders of Female Sexual Arousal -- Disorders of Female Orgasm -- Sexual Pain Disorders -- Erectile Dysfunction: Prevalence and Pathophysiology -- Androgen Deficiency -- Peyronie?s Disease -- Disorders of Ejaculation and Male Orgasm -- Priapism -- The Sexual Health Interview: Male -- The Sexual Health Interview: Female -- Communication About Sexuality and Cancer -- Validated Questionnaires in Female Sexual Function Assessment -- Validated Questionnaires in Male Sexual Function Assessment -- Evaluation of the Female with Sexual Dysfunction -- Evaluation of Male Sexual Dysfunction -- The Impact of Cancer on the Partner's Sexuality -- Gay and Lesbian Patients with Cancer -- The Impact of a Cancer Diagnosis on Sexual Health -- Breast Cancer -- Gynecological Cancers -- Pelvic Surgery for Urological Cancers -- Pelvic Radiation in Men -- Pelvic Radiation in Women -- Impact of Chemotherapy and Hormone Therapy on Female Sexual Health -- Impact of Androgen Deprivation Therapy on Men's Sexual Health -- Colorectal Cancer -- Stem Cell Transplant --Sexual Health in the Terminally Ill -- Survivorship: An Overview -- Nutriceuticals in Sexual Health -- Medical Treatments for Sexual Problems in Women -- Surgical Treatments for Sexual Problems in Women -- Sex Therapy in Female Sexual Dysfunction -- Erectile Dysfunction: Pharmacological Therapy -- Erectile Dysfunction: Devices -- The Management of Premature Ejaculation -- Testosterone Therapy in the Male Cancer Patient -- Sex Therapy in Male Sexual Dysfunction -- Restoring Intimacy in Relationships Affected by Cancer -- Dating and Disclosure for Cancer Survivors.
Keywords: Sexual disorders; Sexual disorders -- Treatment; Sexual health; Cancer -- Treatment -- Complications; Neoplasms -- Complications; Sexual dysfunction, Physiological -- Etiology; Sexual dysfunction, Physiological -- Therapy; Sexual Behavior; Sexuality; Electronic books